Peningkatan Minat dan Hasil Belajar IPAS Melalui Penerapan Model Pembelajaran Kooperatif Tipe Co-Op Co-Op pada Murid Kelas V SD Inpres Balangpunia Kecamatan Pattallassang Kabupaten Gowa - Kasmila, Kasmila; Rahman, Nawir; AS, Husain (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research is a classroom action research that aims to increase interest and learning outcomes of IPAS through the application of the Co-Op Co-Op type cooperative learning model in grade V students of SD Inpres Balangpunia, Pattallassang District, Gowa Regency. The subject of this study is grade V students of SD Inpres Balangpunia, Pattallassang District, Gowa Regency with a total of 22 students, consisting of 13 male students and 9 female students. This research was carried out in two cycles, namely cycle I which was carried out 3 meetings (the first and second meetings for the learning process and the third meeting for the assessment of science and science learning outcomes) and cycle II was also carried out 3 meetings. The two cycles were carried out for 2 months plus summarizing all existing research results. The results showed that students' interest in learning increased significantly between cycle I and cycle II. In the first cycle, students' interest in learning was recorded at only 70%, which shows that most students are not fully interested and motivated to actively participate in learning IPAS. However, after the implementation of the Co-Op Co-Op type cooperative learning model which emphasizes more on collaboration and interaction between students in groups, students' interest in learning increased rapidly in the second cycle to 89%. The results of the study also showed a significant increase in student learning outcomes in cycle II compared to cycle I. In cycle I, student learning completeness only reached 45% with an average score of 66, which shows that most students have not reached the Learning Goal Achievement (KKTP) criteria. This figure reflects that the learning model applied in cycle I is not effective enough in helping students understand the subject matter well. However, after the implementation of the Co-Op Co-Op type cooperative learning model carried out in cycle II, student learning outcomes have improved tremendously. The students' learning completeness increased to 96%, with an average score of 83. This improvement shows that the Co-Op Co-Op model has succeeded in improving students' understanding of the subject matter.